The use of cash transfers for HIV prevention — are we there yet?. Issue 1 (25th March 2016) - Taaffe, Jessica; Cheikh, Nejma; Wilson, David
Abstract : Poverty and social inequality are significant drivers of the HIV epidemic and are risk factors for acquiring HIV. As such, many individuals worldwide are at risk for new HIV infection, especially young women in East and Southern Africa. By addressing these drivers, social protection programmes may mitigate the impact of poverty and social inequality on HIV risk. There is reason to believe that social protection can be used successfully for HIV prevention; social protection programmes, including cash transfers, have led to positive health outcomes and behaviour in other contexts, and they have been used successfully to promote education and increased income and employment opportunities. Furthermore, cash transfers have influenced sexual behaviour of young women and girls, thereby decreasing sexual risk factors for HIV infection. When HIV outcomes have been measured, several randomised controlled trials have shown that indirectly, cash transfers have led to reduced HIV prevalence and incidence. In these studies, school attendance and safer sexual health were directly incentivised through the cash transfer, yet there was a positive effect on HIV outcomes. In this review, we discuss the growth of social protection programmes, their benefits and impact on health, education and economic potential, and how these outcomes may affect HIV risk. We also review the studies that have shown that cash transfers can lead to reduced HIV infection, including study limitations and what questions still remain with regard to using cash transfers for HIV prevention.